Psychological Stress, Cortisol Dysregulation, and Immune Alterations in Breast Cancer: A Biopsychosocial Analysis from a Low- and Middle-Income Country - ABBAS, MUHAMMAD UMAR; ABBAS, AIMAN; IFTIKHAR, SADAF; FARID, GHULAM; AHMED, ADEEL; ALI, AKHTAR (Pakistan Journal of Medical & Health Sciences, 2025)
Background: In Pakistan, breast cancer is the most prevalent malignancy in women and has significant psychosocial and socioeconomic problems that could condition biological stress responses and disease outcomes. Psychological stress triggers hypothalamic-pituitary-adrenal (HPA) axis leading to the secretion of cortisol, which is important in the process of immune regulation and inflammation. Nevertheless, there are few facts on the interaction between psychological stress, cortisol mal-regulation, immune biomarkers, and social determinants in low- and middle-income breast cancer patients. Methods: The study was a multicentred cross-sectional research done in both the public and private oncology hospitals in Punjab, Pakistan. The number of recruited participants was 320 people, 200 of them having histopathological confirmed breast cancer and 120 healthy people. A standardized scale that validated psychological stress was used to assess the stress and salivary and blood samples were measured by cortisol by use of enzyme-linked immunosorbent assay (ELISA). The analysis of immune biomarkers such as secretory immunoglobulin A (sIgA) and inflammatory cytokines was conducted using the standardized analysis approaches. The structured questionnaires and medical records were used to gather sociodemographic and clinical data including socioeconomic status (SES), area deprivation index (ADI) of community, stage of cancer, and mode of treatment. To compare groups and analyze associations, independent t-tests, chi-square tests, ANOVA and correlation analyses were employed. The p-value < 0.05 was assumed to be statistically significant. Results: Breast cancer patients were found to have better cortisol level (13.8 ± 3.4 ng/ml) as opposed to the healthy controls (9.6 ± 2.7 ng/ml; p < 0.001), increased psychological stress (24.2 ± 6.1 vs. 16.8 ± 5.2) and decreased immune biomarkers (sIgA: 112.5 ± 25.6 vs. 138.2 ± 28.4). The cortisol (15.6 ± 3.7 nmol/L), inflammatory cytokines (12.7 ± 3.0) and the stress scores (26.7 ± 6.4) of advanced-stage patients were found to be significantly higher than those of the early-stage patients (p = 0.002). High deprivation areas and the low socioeconomic group accounted a higher percentage of breast cancer patients than the controls (p < 0.001). There was a positive correlation between psychological stress and cortisol levels and inflammatory markers and negative correlation between psychological stress and immune function markers. Conclusion: Breast cancer patients, especially when they have advanced disease and are socioeconomically disadvantaged have great levels of psychological stress, cortisol problems, and immune distortions. The above results indicate a biopsychosocial model between social determinants and stress biology in cancer progression and the need to incorporate psychosocial support in oncology care in low-resource centers.